(untitled) (Scientific journal of the Fergana State University, 2023)
This article presents arguments that as a result of the continuous development of methods of archaeological research, sources of information about objects and materials of the ancient period are expanding, as well as some opinions about such methods of archaeological research as archaeological exploration, archaeological testing and archaeological excavations .